IMPAIRED ENDOTHELIAL FUNCTION AND MICROVASCULAR ADMA IN ANGIOTENSIN II INFUSED RATS: EFFECTS OF TEMPOL - Wang, Dan (2010)
Angiotensin II causes endothelial dysfunction which is associated with cardiovascular risk. We investigated the hypothesis that angiotensin II increases microvascular reactive oxygen species and asymmetric dimethylarginine and switches endothelial function from vasodilator to vasoconstrictor pathways. Acetylcholine-induced endothelium dependent responses of mesenteric resistance arterioles were assessed in a myograph and vascular nitric oxide and reactive oxygen species by fluorescent probes in groups (n=6) of male rats infused for 14 days with angiotensin II (200 ng/kg/min) or given a sham infusion. Additional groups of angiotensin or sham-infused rats were given oral tempol (2 mmol · l(−1)). Angiotensin II infusion increased mean blood pressure (119±5 vs 89±7 mmHg; P<0.005) and plasma malondialdehyde (0.57±0.02 vs 0.37±0.05μmol · l(−1); P<0.035) and decreased maximal endothelium dependent relaxation (18±5 vs 54±6%, P<0.005) and hyperpolarizing (19±3 vs 29±3%, P<0.05) responses and nitric oxide activity (0.9±0.1 vs 1.6±0.2 Units, P<0.01) yet enhanced endothelium dependent contraction responses (23±5 vs 5±5%, P<0.05) and reactive oxygen species production (0.82±0.05 vs 0.15±0.03 units; P<0.01). Angiotensin II decreased the expression of dimethylarginine dimethylaminohydrolase-2 and increased asymmetric dimethylarginine in vessels (450±50 vs 260±35 pmol/mg protein, P<0.01) but not plasma. Tempol prevented any significant changes with angiotensin II. In conclusion, angiotensin redirected endothelial responses from relaxation to contraction, reduced vascular nitric oxide and increased asymmetric dimethylarginine. These effects were dependent on reactive oxygen species and could, therefore, be targeted with effective antioxidant therapy.